Internationalisation, innovation and productivity in services: Evidence from Germany, Ireland and the United Kingdom - Bettina Peters; Rebecca R. Riley; Iulia Siedschlag; Priit Vahter; John McQuinni (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2018)
This paper examines the links between internationalisation, innovation and productivity in service enterprises. For this purpose, we use micro data from the Community Innovation Survey 2008 in Germany, Ireland and the United Kingdom, and estimate an augmented structural model. Our empirical evidence highlights the importance of internationalisation in the context of innovation outputs in all three countries. Our results indicate that innovation in service enterprises is linked to higher productivity. Among the innovation types that we consider, the largest productivity returns were found for marketing innovations.
Keywords: F61; L25; O31; 330; internationalisation of services; innovation; productivity